Absentee tenants and farmland transfers in sub-Saharan Africa: evidence from Malawi. Issue 3 (3rd April 2022) - Ricker-Gilbert, Jacob; Jayne, T. S.; Chamberlin, Jordan
ABSTRACT: We use a unique dataset from Malawi that matches tenants and their landlord counterparts to document the role played by absentee tenants, i.e. tenants who reside outside the area where the rented land is located. We found that non-local tenants made up 22% of the tenants in our sample. A significant subset of them had higher off-farm income and significantly more assets than did other tenants. Conversely, we found that 76% of landlords rented land because they needed cash. Our results highlight the fact that some rental transactions reinforce power imbalances and may exacerbate risks faced by poorer landlords.